Curcumin induces DNA damage by mediating homologous recombination mechanism in triple negative breast cancer - KAYA, ÖZLEM TUĞÇE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
Curcumin has a therapeutic potential activity through modulation of different signaling pathways in various types of cancer. However, the relationship between the efficacy of curcumin and the homologous recombination (HR) mechanism which plays important roles in the repair of double strand DNA (dsDNA) breaks remains uncertain. Herein, we explored curcumin-dependent dsDNA breaks and the association of curcumin with HR mechanism in triple negative breast cancer (TNBC). The cytotoxic and therapeutic activity of curcumin on HCC1937 (BRCA1 mutant), MDA-MB-231 (BRCA1 wild type) TNBC and HUVEC control cell lines were assessed. Then, the expression level and subcellular localization of H2AX, PARP1, BRCA1 and RAD51 were detected by RT-PCR and immunofluorescence analysis. Furthermore, ultrastructural changes of cell death were observed by TEM. Our findings for the first time demonstrated that curcumin?s therapeutic activity was more pronounced in HCC1937 cells through the suppression of HR mechanism and the induction of dsDNA breaks. Consequently, curcumin based therapy could benefit in patients with TNBC particularly especially in women with a BRCA1 mutation.
Keywords: BRCA1; APOPTOSIS; REPAIR; CELLS